On the Formal Relationship between the Synthetic Past Tenses in Macedonian and Its Role in the Evolution of the Conjugational Unit - Elson, Mark J. (Zeitschrift für Balkanologie, 2005)
This paper proceeds from structural differences in the synchronic morphology of the synthetic past tenses (i.e., the aorist past and the imperfect past) which oppose the Kumanovo dialects of Macedonian to other Macedonian dialects. I argue that, historically, all such differences can be explained by the fate of [x], a segment which occurred in the desinential portion of past tense forms with the meaning ‘past’, and which was subject, through sound change, to loss and/or reinterpretation as [v].The result was dialectal differences in the phonemic configuration of past tense desinential strings which, over time, led to the structural differences which oppose Kumanovo dialects to others synchronically.